Islamic Educational Leadership in the Era of Digital Transformation: Developing Adaptive Leadership Competencies for School Principals - Mowafg Masuwd; Markhabat Bolat; Mohammad Ahmad Bani Amer (Ar-rayyan: Journal Of Islamic Education, 2025)
Digital transformation has fundamentally changed educational management, requiring school leaders to possess adaptive leadership competencies capable of responding to technological innovation and organizational change. Nevertheless, limited research has examined Islamic educational leadership from the perspective of digital transformation. This study aims to formulate an adaptive leadership model for principals of Islamic educational institutions in the digital era. A qualitative multiple-case study was conducted across several Islamic schools recognized for implementing digital innovation. Data were collected through interviews, observations, and document analysis, followed by thematic analysis. The findings indicate that successful Islamic educational leadership combines visionary planning, technological competence, collaborative decision-making, ethical governance, and Islamic values-based management. School principals who successfully integrate these competencies create innovative organizational cultures while maintaining strong religious identity and institutional integrity. The proposed leadership model also supports sustainable school improvement through continuous professional development and digital governance. The novelty of this research is the formulation of an Adaptive Digital Islamic Leadership Model that integrates contemporary leadership theory with Islamic educational values, offering a comprehensive framework for leading Islamic schools in the era of educational digitalization